Correlation of localization and size of the parathyroid glands by ultrasound and intraoperative findings in hyperparathyroidism - Sabrina Uščuplić; Šekib Umihanić; Hasan Altumbabić; Almir Salkić; Merima Kasumović; Almedina Ramaš (Medicinski glasnik, 2023)
Aim: To determine a correlation between the localization of the parathyroid gland (PTG), based on ultrasound (US) examination and the operative findings, as well as the correlation between the size of the parathyroid glands measured by ultrasonography (USG) with pathological findings+, and prevalence of enlarged parathyroid glands in various forms of hyperparathyroidism. Methods: A total of 83 patients with hyperparathyroidism who had undergone parathyroidectomy over a period of seven years were included in the study. US examinations of the neck and scintigraphy were performed before surgery in 83 and 42 patients, respectively. In the pathohistological analysis, in addition to diagnosis, the size and weight of the parathyroid gland were measured. Results: US examination revealed 125 enlarged parathyroid glands and two normal-sized glands. Scintigraphy revealed 52 enlarged and three normal-sized parathyroid glands. Enlarged parathyroid glands were more frequently found in the projection of the lower pole thyroid glands. A significantly higher number of enlarged upper parathyroid glands were found by the operative findings than by US. There was no statistically significant difference in the diagnosis of enlarged parathyroid glands in all three forms of hyperparathyroidism. There was a positive correlation between the size of the parathyroid glands obtained by US and the size of the operative finding (κ=0.51; p=0.00 and p<0.0005, respectively). The relationship between parathyroid gland size measured by ultrasound and pathological analysis showed a positive correlation. Conclusion: Ultrasound was useful in evaluating enlarged parathyroid glands, especially in combination with scintigraphy.
Keywords: intraoperative identification; parathyroid localization; parathyroidectomy; scintigraphy; surgeon